2010
DOI: 10.3109/09553002.2010.537432
|View full text |Cite
|
Sign up to set email alerts
|

The production and composition of rat sebum is unaffected by 3 Gy gamma radiation

Abstract: Purpose The aim of this work was to use metabolomics to evaluate sebum as a source of biomarkers for gamma-radiation exposure in the rat, and potentially in man. Proof of concept of radiation metabolomics was previously demonstrated in both mouse and rat urine, from the radiation dose- and time-dependent excretion of a set of urinary biomarkers. Materials and methods Rats were gamma-irradiated (3 Gy) or sham irradiated and groups of rats were euthanised at 1 h or 24 h post-irradiation. Sebum was collected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
(69 reference statements)
2
10
0
Order By: Relevance
“…1, Table 1). This corresponds well with published data of Lanz et al [61], who demonstrated that the longest detected FA in sebaceous lipids was C 26 , and a paper by Pappas et al [62], where FA from C 12 to up to C 22 were reported instead of C 34 FA moieties in meibomian lipids (Table 2). Lastly, a detailed analysis of human sebaceous lipids conducted by Camera et al [63] demonstrated that FA residues of CE found in sebum ranged from C 14 to C 18 , DAG were mostly of C 30 to C 35 nature (two FA residues combined), TAG barely reached C 57 (three FA residues combined), while WE were based on C 16:1 FA esterified to C 12 to C 26 FAL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1, Table 1). This corresponds well with published data of Lanz et al [61], who demonstrated that the longest detected FA in sebaceous lipids was C 26 , and a paper by Pappas et al [62], where FA from C 12 to up to C 22 were reported instead of C 34 FA moieties in meibomian lipids (Table 2). Lastly, a detailed analysis of human sebaceous lipids conducted by Camera et al [63] demonstrated that FA residues of CE found in sebum ranged from C 14 to C 18 , DAG were mostly of C 30 to C 35 nature (two FA residues combined), TAG barely reached C 57 (three FA residues combined), while WE were based on C 16:1 FA esterified to C 12 to C 26 FAL.…”
Section: Discussionsupporting
confidence: 92%
“…Human ML are longer than even already highly elongated lipids of sebum (Fig. 1 and references [6163]), which might be caused by either alterations in the substrate and/or product specificity of known enzymes through effectors or post-translational modifications, or the existence of isozymes with altered structures and catalytic activities. The same can be argued for the branched lipids, as we do not know how branching of FA and FAL impacts specificity of enzymes that elongate FA or produce FAL, WE, CE, OAHFA, CHL-OAHFA, DiAD and other lipids found in meibum.…”
Section: Discussionmentioning
confidence: 99%
“…36) Moreover, urine has also been used to describe the course of a metabolic phenotype in rats after irradiation; it has showed effects on kidney functions following oxidative stress. 12) Other biological fluids, such as sebum, have also been explored as biomarker sources 37) in experiments demonstrating the diversity of potentially usable biofluids.…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the samples was stored at −80°C under nitrogen. Samples were analyzed by GCMS as previously described (28). For quantitation of fatty acids, calibration curves were prepared with heptadecanoic acid as internal standard (see above) and a fatty acid concentration range of 0–1,000 μmol/l.…”
Section: Methodsmentioning
confidence: 99%